Designing amplifier circuits - Feucht, Dennis (Feucht, Dennis. Analog circuit design series ;, 2010)
Synopsis: The Analog Circuit Design Series set reduces the concepts of analog electronics to their simplest, most obvious form which can easily be applied (even quantitatively) with minimal effort. The emphasis of the set is to help you intuitively learn through inspection how circuits work and apply the same techniques to circuits of the same class. This first volume, Designing Amplifier Circuits, presents the basic principles of transistor circuit analysis, basic per-stage building blocks, and feedback. The content is restricted to quasi-static (low-frequency) considerations, to emphasize basic topological principles. The reader will be able to analyze and design multi-stage amplifiers with feedback, including calculation and specification of gain, input and output resistances, including the effects of transistor output resistance. Of note is the presentation of feedback analysis, a subject rarely covered by other books, with insights and from angles that will reduce to analysis by inspection for readers. Some circuit transformations outlined within are especially helpful in reducing circuits to simpler forms for analysis. They are usefully applied in considering transistor circuits for which collector-emitter (or drain-source) resistance is not negligible, another often omitted topic which this book details.